Islamic Custom of Letter and Seal in Sarakata Manuscript “Surat-Surat dari Aceh” - Rakhadiyanti, Mustika Ayu; Limbong, Priscila Fitriasih (Center for Research and Development of Religious Literature and Heritage, 2020)
This paper presents a study on Sarakata manuscripts from the collection of the National Library of the Republic of Indonesia. The Sarakata analyzed in this research is entitled